Characterization of uterine involution using B-mode ultrasonography, color Doppler and elastography (acoustic radiation force impulse) for assessing postpartum in Santa Inês ewes - Mariano, Renata Sitta Gomes [UNESP]; Santos, Victor José Correia [UNESP]; Taira, Augusto Ryonosuke [UNESP]; da Silva, Priscila Del Aguila [UNESP]; Rodriguez, Mariana Garcia Kako [UNESP]; Padilha-Nakaghi, Luciana Cristina [UNESP]; Simões, Ana Paula Rodrigues [UNESP]; Maronezi, Marjury Cristina [UNESP]; Avante, Michelle Lopes [UNESP]; Uscategui, Ricardo Andres Ramirez [UNESP]; Lima, Bruna Bressianini [UNESP]; Feliciano, Marcus Antônio Rossi; et al. (FapUNIFESP (SciELO), 2023)
The aim of this study was to investigate uterine involution using ultrasonography techniques during postpartum. Postpartum ultrasonography evaluation (B-mode, color Doppler and Acoustic Radiation Force Impulse elastography) of the uterus was performed by transabdominal approach at immediate after birth and sequentially every 48 hours, during 30 days. The uterine echotexture did not present significant variations (P?>0.05) being homogeneous in most evaluations; echogenicity of the uterus increased along the evaluation period (P =0.0452). Progressive and remarkable decrease of the total uterine diameter (UD) were observed (P <0.0001), especially during the first days postpartum. The thickness of uterine wall gradually decreased, as well the endometrial, myometrium and lumen diameters (P <0.0001). Uterine blood flow was assessed by Doppler and decreased during postpartum period, being significantly lower (P=0.0225) on the 30th day of postpartum. Uterine parenchyma presented as homogeneous dark areas (not deformable) on qualitative ultrasound elastography and the means shear velocity values of the uterine wall on quantitative elastography did not differ. This is the first study that evaluate the stiffness of uterine wall in healthy ewes, providing baseline data about quantitative and qualitative stiffness of the normal uterus, and it may be a useful tool for early diagnosis of uterine alterations during the postpartum period, using the reference parameter established for the assessment of uterine integrity during postpartum period.
Keywords: puerperium; sheep; uterine involution; uterine stiffness